System design single vendor marketplace - Betri, Tigus Juni (Research in Education and Technology (REGY), 2023)
Single Vendor Marketplace is a web-based application or mobile-based application where there is only one seller who provides products. Seller sales transactions only involve sellers and buyers directly without any third parties or intermediaries. The advantage of this system is that you can manage your profits directly yourself. Some also call this application a stand-alone website. The revised Borg and Gall research and development method allows the system design of this information system to be completed well. This design process has several stages. The Borg and Gall development model has a series of steps or stages consisting of information gathering, planning stage, initial product design development stage, field trial stage, main product revision stage, field test stage, operational product revision, field testing stage, product revision stage final, and also the socialization and implementation stages. A structured system design is needed at this stage where in general the design consists of system design, database design, interface design, and prototype product design. It is hoped that this marketplace application with a single vendor system can improve the quality of management thereby increasing business profits.